The African National Congress and the Regeneration of Political Power - Booysen, Susan (Wits University Press, 2011)
The ANC is a party-movement that draws on its liberation credentials yet is conflicted by a multitude of weaknesses, factions and internal succession battles. Booysen constructs her analysis around the ANC's four faces of political power - organisation, people, political parties and elections, and policy and government - and explores how, since 1994, it has acted to continuously regenerate its power.